Electronic Transport Parameter of Carbon Nanotube MetalSemiconductor OnTube Heterojunction - Sukirno Sukirno; Satria Zulkarnaen Bisri; Irmelia Irmelia (Journal of Mathematical and Fundamental Sciences, 2009)
Carbon Nanotubes research is one of the top five hot research topics in physics since 2006 because of its unique properties and functionalities, which leads to widerange applications. One of the most interesting potential applications is in term of nanoelectronic device. Carbon nanotubes heterojunction has been modeled, which was built from two different carbon nanotubes, that one is metallic and the other one is semiconducting. There are two different carbon nanotubes metalsemiconductor heterojunction. The first one is built from CNT(10,10) as metallic carbon nanotube and CNT (17,0) as semiconductor carbon nanotube. The other one is built from CNT (5,5) as metallic carbon nanotube and CNT (8,0). All of the semiconducting carbon nanotubes are assumed to be a pyridinelike Ndoped. Those two heterojunctions are different in term of their structural shape and diameter. It has been calculated their charge distribution and potential profile, which would be useful for the simulation of their electronic transport properties. The calculations are performed by using selfconsistent method to solve NonHomogeneous Poisson's Equation with aid of Universal Density of States calculation method for Carbon Nanotubes. The calculations are done by varying the doping fraction of the semiconductor carbon nanotubes The electron tunneling transmission coefficient, for low energy region, also has been calculated by using WentzelKramerBrillouin (WKB) approximation. From the calculation results, it is obtained that the charge distribution as well as the potential profile of this device is doping fraction dependent.